Canada and its impact on the global food crisis - Kazakova, Nadia; Aleksenko, Volodumur (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
Today, the most important issue is: will our planet have the resources to feed a rapidly growing population? Agricultural technologies are improved, but there is still not enough food for all and in many countries people are starving. The Government of Canada is one of the strongest supporters of the World Food Programme and consistently in among the top three donors of food over the past five years..